Flexo-Pyrophotronic Effect Modulated Giant Near Infrared Photoresponse from VO2-Based Heterojunction for Optical Communication - Kumar, Mohit; Kim, Dukhwan; Seo, Hyungtak (Small Methods, 2024)
The flexoelectric phenomenon, which occurs when materials undergo mechanical deformation and cause strain gradients and a related spontaneous electric polarization field, can result in wide variety of energy- and cost-saving mechano-opto-electronics, such as night vision, communication, and security. However, accurate sensing of weak intensities under self-powered conditions with stable photocurrent and rapid temporal response remains essential despite the challenges related to having suitable band alignment and high junction quality. Taking use of the flexoelectric phenomena, it is shown that a centrosymmetric VO2-based heterojunction exhibits a self-powered (i.e., 0 V), infrared (λ = 940 nm) photoresponse. Specifically, the device shows giant current modulation (103%), good responsivity of >2.4 mA W−1, reasonable specific detectivity of ≈1010 Jones, and a fast response speed of 0.5 ms, even at the nanoscale modulation. Through manipulation of the applied inhomogeneous force, the sensitivity of the infrared response is enhanced (> 640%). Ultrafast night optical communication like Morse code distress (SOS) signal sensing and high-performing obstacle sensors with potential impact alarms are created as proof-of-concept applications. These findings validate the potential of emerging mechanoelectrical coupling for a wide variety of novel applications, including mechanoptical switches, photovoltaics, sensors, and autonomous vehicles, which require tunable optoelectronic performance.
Keywords: Flexoelectric; Flexoelectric effects; Mechanical deformation; Morse codes; Near Infrared; Near infrared light; Near-infrared; Night optical communication; Photoresponses; Self-powered; flexoelectric effect; Morse code; near-infrared light; night optical communication; photodetectors